The Effect of Feed Type Different from the Amount, Growth and Life of Mangrove Crab (Scylla serrata) that Lay Eggs - Pinta M Hutagalung; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTFeed is one of the important factors to produce maximum production in the cultivation of egg crabs. This study aims to determine the effect of different types of feed on the number of mangrove crabs (Scylla serrata) that lay eggs, absolute weight growth, specific growth rates, and survival. The method of this study is an experimental method (experiment) using a one-factor Completely Randomized Design (CRD) with 4 levels of treatment 3 replications so that 12 units of the experiment were obtained. Each treatment given is P1 = Fly Fish 6% / body weight, P2 = Squid 6% / body weight, P3 = Shrimp 6% / body weight, and P4 = Lemuru Fish 6% / body weight. The crabs used are 180-190 g in size stocked in basket containers with stocking densities for each basket that is 1 tail. Maintenance lasts for 20 days and feed is given as much as 6% of body weight, frequency of feeding twice a day. The parameters observed included observing the number of spawning crabs, absolute weight growth, specific growth rate, feed efficiency, feed conversion ratio, survival rate and water quality. The results showed that the feeding of shrimp feed was the best treatment resulting in the number of mangrove crabs laying as many as 10 tails, absolute weight growth of 93.29 g, specific growth rate of 2.04%, feed efficiency 53.26%, feed conversion 1.88 and livelihood level 83.33%. Based on the results of the study concluded that the provision of different types of feed significantly affected the number of spawning crabs, had a very significant effect on growth and did not significantly affect the survival of mangrove crabs (Scylla serrata) which lay eggs.Keywords : Fresh feed; The number of crabs lay eggs; Growth; Life-long rate; Mangrove Crab; Scylla serrata